The Labyrinth of Star Formation - Stamatellos, Dimitris; Goodwin, Simon; Ward-Thompson, Derek (Astrophysics and Space Science Proceedings, 2014)
This volume contains the proceedings from the conference "The Labyrinth of Star Formation" that was held in Crete, Greece, in June 2012, to honour the contributions to the study of star formation made by Professor Anthony Whitworth of Cardiff University. The book covers many aspects of theoretical and observational star formation: low-mass star formation; young circumstellar discs; computational methods; triggered star formation; the stellar initial mass function; high-mass star formation; and stellar clusters. Each section starts with a review paper, followed by papers discussing recent theoretical and observational work. This volume summarises our current understanding of star formation and is useful for both graduate students and researchers alike.